Corrigendum: Design and preliminary feasibility study of a Soft Robotic Glove for hand function assistance in Stroke Survivors [Front. Neurosci., 11, (2017) (547)] DOI: 10.3389/fnins.2017.00547 - Yap, H.K (Frontiers Media, 2020)
10.3389/fnins.2018.00323